Land Evaluation for Alternate Land Use Planning of Sugarcane Growing Soils of Chittoor District in Andhra Pradesh - M.V.S. Naidu, P.A. Visalakshi Devi and (Journal of the Indian Society of Soil Science, 2016)
Seventeen typical pedons representing major sugarcane growing soils of Chittoor district were studied and evaluated by using qualitative and quantitative methods. The qualitative method employed were USDA land capability classification and land suitability classification, while the quantitative evaluation method includes Riquier’s parametric approach. The land evaluation methods indicated that information on production potential of soils provide a basis for comparison among different soils. The soils of study area were classified into land capability classes IV, V and VI. However, the land suitability evaluation suggested that these sugarcane growing soils were moderately suitable (S2) (P2, P5, P6, P13 and P16) and moderate to marginally suitable (S2-S3) (P1, P3, P4, P7, P8, P9, P10, P11, P12, P14, P15 and P17) for growing sugarcane crop. Riquier’s parametric approach was found to be good indicator for identification of production potential of sugarcane growing soils. The land evaluation study revealed that, characteristics and suitability of these soils for sugarcane crop were highly variable, hence their management must be site specific. Soil management strategies based on crop residue retention, nutrient recycling, minimum tillage, crop rotation, cover crops and inter cropping not only helps to conserve soil and water more effectively in sugarcane growing soils but also increase organic matter content and improve fertilizer use efficiency. Adoption of suggested ameliorative measures and land use not only improves the yields but also sustains the soil productivity.